P06 Bacterial Meningitis in Babies 0–90 Days of Age: A UK and Republic of Ireland Prospective Study. (4th June 2013) - Okike, I; Henderson, K; Blackburn, R; Muller-Pebody, B; Anthony, M; Ninis, N; Johnson, A; Heath, P
Abstract : Background and aims: Meningitis in the first 3 months of life is associated with significant mortality and morbidity. Previous UK studies were conducted in the 1980s and 1990s. It is important to define the current burden of disease in order to prioritise treatment and prevention strategies. Methods: Cases were identified prospectively by active surveillance through the British Paediatric Surveillance Unit, routine microbiological surveillance through the Health Protection Agency and via parents of cases through meningitis and Group B streptococcus (GBS) support charities. The surveillance period was July 2010 – July 2011. Results: 365 cases were identified, equivalent to a total incidence of 0.38/1000 live-births (95% CI: 0.35- 0.42); for late-onset (n = 252) was 0·27 per 1000 (0·23—0·30), and for early-onset (n = 113) was 0·12 per 1000 (0·10—0·14). The male to female ratio was 1.3:1. The median age of disease (IQR) was 14 days (3–36). The majority of cases (62%) were admitted from home. Lumbar puncture was performed in 319/329 (97%) of the cases. The timing of LP was available in 307 (96%) and was before the first dose of antibiotics in only 110/306 (36%) of the cases. Of the 304 organisms isolated 151 (50%) were Group B Streptococcus (GBS), 40 (13%) E coli, 28 (9%) Streptococcus pneumoniae (SPn), 24 (8%) Meningococcus, 11 (4%) Listeria monocytogenes, 24 (8%) other Gram positive bacteria and 24 (8%) other Gram negative bacilli. Overall, blood culture was negative in 134/329 (41%) of cases of meningitis. At the time of reporting or discharge 25 babies had died [CFR 7.6, 95% CI: 5.0–11.0). Spn-specific CFR (19%) was significantly higher than GBS-Specific CRF (5%). An acute complication was identified in 78/304 (26%) of the survivors. Conclusion: There remains a significant burden of bacterial meningitis in the first 3 months of life. The leading causes remain unchanged for the past three decades. Further work should be done on the prevention and early management of cases